Activation of autophagy is required for clearance of mitochondrial ROS in patients with asthenozoospermia - Xiaona Wang; Shiyuan Huang; Yu Zhao; Hua Chen; Linzhi Yan; Hongshan Ge; Xinmei Wu (PeerJ)
Autophagy is regarded as an essential process for maintaining cell homeostasis. However, its role in the regulation of sperm motility is still less understood. In this study, we found that mitochondrial oxidative species (mROS) levels were elevated, but ATP levels and mitochondrial membrane potential (MMP) levels were reduced in human sperm with low motility (also called asthenozoospermia, AS) as compared to normal human sperm (normal sperm, NS). Immunocytochemistry staining showed that LC3 was mainly located in the neck of sperm. Western blot analysis showed that AS patients had elevated levels of the autophagy-related proteins LC3, Atg5, Atg7, and Beclin1. Flow cytometry showed that 3-MA treatment reduced sperm motility and MMP, but increased mROS. The results indicate that autophagy is essential for the clearance of mROS in sperm and the maintenance of mitochondrial function.